Neonatal rotavirus vaccine (RV3-BB) immunogenicity and safety in a neonatal and infant administration schedule in Malawi: a randomised, double-blind, four-arm parallel group dose-ranging study. Issue 5 (May 2022) - Witte, Desiree; Handley, Amanda; Jere, Khuzwayo C; Bogandovic-Sakran, Nada; Mpakiza, Ashley; Turner, Ann; Pavlic, Daniel; Boniface, Karen; Mandolo, Jonathan; Ong, Darren Suryawijaya; Bonnici, Rhian; Justice, Frances; et al.
Summary: Background: Rotavirus vaccines reduce rotavirus-related deaths and hospitalisations but are less effective in high child mortality countries. The human RV3-BB neonatal G3P[6] rotavirus vaccine administered in a neonatal schedule was efficacious in reducing severe rotavirus gastroenteritis in Indonesia but had not yet been evaluated in African infants. Methods: We did a phase 2, randomised, double-blind, parallel group dose-ranging study of three doses of oral RV3-BB rotavirus vaccine in infants in three primary health centres in Blantyre, Malawi. Healthy infants less than 6 days of age with a birthweight 2·5 to 4·0 kg were randomly assigned (1:1:1:1) into one of four treatment groups: neonatal vaccine group, which included high-titre (1·0 × 10 7 focus-forming unit [FFU] per mL), mid-titre (3·0 × 10 6 FFU per mL), or low-titre (1·0 × 10 6 FFU per mL); and infant vaccine group, which included high-titre (1·0 × 10 7 FFU per mL) using a computer generated code (block size of four), stratified by birth (singleton vs multiple). Neonates received their three doses at 0–5 days to 10 weeks and infants at 6–14 weeks. Investigators, participant families, and laboratory staff were masked to group allocation. Anti-rotavirus IgA seroconversion and vaccine take (IgA seroconversion and stool shedding) were evaluated. Safety was assessed in all participants who received at least one dose of vaccine or placebo. The primary outcome was the cumulative IgA seroconversion 4 weeks after three doses of RV3-BB in the neonatal schedule in the high-titre, mid-titre, and low-titre groups in the per protocol population, with its 95% CI. With the high-titre group as the active control group, we did a non-inferiority analysis of the proportion of participants with IgA seroconversion in the mid-titre and low-titre groups, using a non-inferiority margin of less than 20%. This trial is registered at ClinicalTrials.gov (NCT03483116 ). Findings: Between Sept 17, 2018, and Jan 27, 2020, 711 participants recruited were randomly assigned into four treatment groups (neonatal schedule high titre n=178, mid titre n=179, low titre n=175, or infant schedule high titre n=179). In the neonatal schedule, cumulative IgA seroconversion 4 weeks after three doses of RV3-BB was observed in 79 (57%) of 139 participants in the high-titre group, 80 (57%) of 141 participants in the mid-titre group, and 57 (41%) of 138 participants in the low-titre group and at 18 weeks in 100 (72%) of 139 participants in the high-titre group, 96 (67%) of 143 participants in the mid-titre group, and 86 (62%) of 138 of participants in the low-titre. No difference in cumulative IgA seroconversion 4 weeks after three doses of RV3-BB was observed between high-titre and mid-titre groups in the neonatal schedule (difference in response rate 0·001 [95%CI −0·115 to 0·117]), fulfilling the criteria for non-inferiority. In the infant schedule group 82 (59%) of 139 participants had a cumulative IgA seroconversion 4 weeks after three doses of RV3-BB at 18 weeks. Cumulative vaccine take was detected in 483 (85%) of 565 participants at 18 weeks. Three doses of RV3-BB were well tolerated with no difference in adverse events among treatment groups: 67 (39%) of 170 participants had at least one adverse event in the high titre group, 68 (40%) of 172 participants had at least one adverse event in the mid titre group, and 69 (41%) of 169 participants had at least one adverse event in the low titre group. Interpretation: RV3-BB was well tolerated and immunogenic when co-administered with Expanded Programme on Immunisation vaccines in a neonatal or infant schedule. A lower titre (mid-titre) vaccine generated similar IgA seroconversion to the high-titre vaccine presenting an opportunity to enhance manufacturing capacity and reduce costs. Neonatal administration of the RV3-BB vaccine has the potential to improve protection against rotavirus disease in children in a high-child mortality country in Africa. Funding: Bill & Melinda Gates Foundation, Australian Tropical Medicine Commercialisation Grant.